The Experience of People with Visual Impairments with Web Chatbots - Diego de Oliveira, Rodrigo; Leite Ribeiro Okimoto, Maria Lucia (Cadernos de Educação Tecnologia e Sociedade, 2022)
This article deals with accessibility in web chatbots for people with visual impairments, with the aim of identifying barriers that prevent the use, access or provide a bad experience for these users in the face of this type of conversational interface. Chatbots can be defined as services or types of programs powered by rules or artificial intelligence, which seek to simulate the dialogue of a human being through text and/or voice-based interactions. The method used to identify accessibility barriers consisted of carrying out an exploratory and qualitative study, based on twelve interviews with visually impaired people of different profiles. The results showed that blind people who had experiences with chatbots faced a series of difficulties and frustrations, but felt comfortable interacting with a robot instead of a human being. It was concluded that, despite the barriers encountered, blind people believe in the inclusive potential of technology and there is a need to deepen the theme to design more accessible interfaces.